Variants in the Glucocorticoid Receptor gene (NR3C1), asthma control and serum cytokine levels - de,Santana MBR; Cruz,AA; De,Araujo JLF; Tugores,RM; Teixeira,HMP; de,Jesus TS; Pimentel,G; Santana,CVN; Kermani,NZ; Chung,KF; Adcock,IM; Souza-Machado,A; et al. (Respiratory Medicine, 2026)
IntroductionAsthma is a heterogeneous disease usually treated with inhaled corticosteroids (ICS) and long-acting beta2 agonists. However, not all individuals achieve adequate control with ICS.AimTo identify genetic variants in the glucocorticoid receptor gene (NR3C1) associated with asthma endophenotypes, bronchodilator reversibility, and asthma control under medium-to-high ICS doses.MethodsAssociation analyses were performed in 365 patients with moderate-to-severe asthma, 383 with mild asthma, and 330 non-asthmatic individuals. Asthma severity was defined by the need for regular treatment with medium-to-high ICS doses. Bronchodilator reversibility was defined as an increase of ≥200 ml and ≥12 % in FEV1 from baseline. Asthma control was assessed using the ACQ6 score. Serum cytokine concentrations were measured with Luminex.ResultsThe A allele of rs2918417 was associated with reduced risk of moderate-to-severe asthma (OR: 0.50; 95 % CI: 0.26–0.98) and fewer exacerbations (OR: 0.54; 95 % CI: 0.30–0.96); GA/AA genotypes showed lower IL-8 and IL-13 levels compared to GG. The G allele of rs6877893 decreased the risk of uncontrolled asthma in the recessive model (OR: 0.53; 95 % CI: 0.29–0.98), with GG carriers showing reduced IL-17A. Conversely, the A allele of rs4585488 increased risk of uncontrolled asthma (OR: 4.42; 95 % CI: 1.06–18.48), and the C allele of rs4912650 was linked to poor control (OR: 1.64; 95 % CI: 1.01–2.69). The G allele of rs4607376 was associated with lack of bronchodilator reversibility (OR: 1.51; 95 % CI: 1.05–2.17) and asthma exacerbations (OR: 1.37; 95 % CI: 1.01–1.87).ConclusionsNR3C1 variants are associated with moderate-to-severe asthma, poor control, lack of bronchodilator reversibility, and differential cytokine profiles.